The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acsami.7b03371
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-Modified MoS2 Nanoflakes as a Platform for Combinational Gene Silencing and Photothermal Therapy of Tumors

Abstract: Exploitation of novel hybrid nanomaterials for combinational tumor therapy is challenging. In this work, we synthesized dendrimer-modified MoS nanoflakes for combinational gene silencing and photothermal therapy (PTT) of cancer cells. Hydrothermally synthesized MoS nanoflakes were modified with generation 5 (G5) poly(amidoamine) dendrimers partially functionalized with lipoic acid via disulfide bond. The formed G5-MoS nanoflakes display good colloidal stability and superior photothermal conversion efficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 52 publications
0
78
0
Order By: Relevance
“…This MoS 2 –PEI–PEG nanocomposite was demonstrated to be highly biostable and displayed low toxicity in cells, which provides a spatiotemporally controllable and effective platform to deliver gene materials into cells. Additionally, G5‐LA‐modified MoS 2 via the disulfide bonds was presented by Kong et al, and it was shown to have good colloidal stability, excellent photothermal conversion efficiency, and photothermal stability . It was further verified that these G5‐LA–MoS 2 nanoflakes were able to deliver Bcl‐2 siRNA to cancer cells based on the dendrimer amines on the surface, as the dendrimer amines with positive surface potential can deliver negatively charged siRNA through electrostatic interactions.…”
Section: Functionalization Of Tmdcmentioning
confidence: 86%
See 1 more Smart Citation
“…This MoS 2 –PEI–PEG nanocomposite was demonstrated to be highly biostable and displayed low toxicity in cells, which provides a spatiotemporally controllable and effective platform to deliver gene materials into cells. Additionally, G5‐LA‐modified MoS 2 via the disulfide bonds was presented by Kong et al, and it was shown to have good colloidal stability, excellent photothermal conversion efficiency, and photothermal stability . It was further verified that these G5‐LA–MoS 2 nanoflakes were able to deliver Bcl‐2 siRNA to cancer cells based on the dendrimer amines on the surface, as the dendrimer amines with positive surface potential can deliver negatively charged siRNA through electrostatic interactions.…”
Section: Functionalization Of Tmdcmentioning
confidence: 86%
“…They found that these LA‐PEG‐modified TMDC materials all exhibit desirable compatibility in a physiological environment with additional excellent biomedical applications, such as multimodal imaging and synergistic therapy for cancer treatment. In addition to PEG, other polymers such as poly(acrylic acid) (PAA), polyethylenimine (PEI), combined PAA–PEG or PEI–PEG, or polyaniline (PANI), as well as generation‐5 poly(amidoamine) dendrimers–lipoic acid (G5‐LA) are also widely used in the process for functionalization of TMDCs. For example, similar to LA‐PEG functionalization, effective polymer conjugation via the disulfide bond was reported by Kim et al, in which MoS 2 was modified with LA‐modified PEI, as well as thiolated PEG polymers (MoS 2 –PEI–PEG) ( Figure a) .…”
Section: Functionalization Of Tmdcmentioning
confidence: 99%
“…[230] MoS 2 nanoflakes were functionalized with lipoic acid-conjugated generation 5 (G5) poly(amidoamine) (PAMAM) dendrimers for transfection of Bcl-2 (B-cell lymphoma-2) siRNA into 4T1 cells. [230] MoS 2 nanoflakes were functionalized with lipoic acid-conjugated generation 5 (G5) poly(amidoamine) (PAMAM) dendrimers for transfection of Bcl-2 (B-cell lymphoma-2) siRNA into 4T1 cells.…”
Section: Photothermal Therapy and Drug/gene Deliverymentioning
confidence: 99%
“…Overall, this strategy may allow a reduction in doses of iron oxides, magnetic field strength, and NIR excitation power to comply with in vivo settings. TiO 2-x treatment with 808 nm (1 W cm −2 ) irradiation www.advancedsciencenews.com www.advtherap.com MoS 2 Exfoliation Chitosan 80 nm (l) 4-6 nm (t) -PTT, drug delivery, CT imaging [187] MoS 2 Exfoliation -14.7 nm (hd) -PDT, down-and upconversion fluorescence Imaging [188] MoS 2 Exfoliation LA-PEG 50 nm (l) 2 nm (t) 28.4 L g −1 cm −1 at 800 nm PTT, drug delivery [191] MoS 2 Exfoliation BSA 89 nm (l) 5-15 nm (t) -PTT, drug delivery [192] MoS 2 Ionic liquid grinding Chitosan 120 nm (l) 1.4 nm (t) 62.6 L g −1 cm −1 at 800 nm PTT [194] MoS 2 Solvothermal PEG 79.2 nm (l) 0.29 nm (t) -PTT [197] MoS 2 Exfoliation -0.8 µm (l) 1.6 nm (t) 29.2 L g −1 cm −1 at 800 nm PTT [199] MoS 2 Solvothermal LA-PEG 90 nm (l) -PTT [201] MoS 2 Hydrothermal Polyacrylic acid LA-PEG 90 nm (l) -PTT [203] MoS 2 Sonication BSA 181 ± 3 nm (l) (hd) 10.65 nm (t) -PA imaging [209] MoS 2 Exfoliation DMSA-IONP-PEG-Amine LA-PEG 50-200 nm (l) -PTT, PA, MRI, and PET imaging [211] MoS 2 Hydrothermal Fe 3 O 4 PEG 190.1 nm (hd) -PTT, PA, and MRI imaging [213] MoS 2 Solvothermal Polyaniline PEG 21.5 ± 3.9 nm (hd) -PTT, RT, PA, and CT imaging [215] MoS 2 Exfoliation PEG-amine Mesoporous silica DOX 450 nm (hd) -PTT, drug delivery [223] MoS 2 Exfoliation PEI-HA DOX NOTA-64 Cu 30-50 nm (l) 5-7 nm (t) -PTT, drug delivery [224] MoS 2 Solvothermal PLGA oleosol DOX 100 nm (l) -PTT, drug delivery [225] MoS 2 Exfoliation LA-PEG PEI 90 nm (hd) -PTT, gene delivery [226] MoS 2 Exfoliation LA-PEI SH-PEG 100-150 nm (l) 6-8 nm (t) -PTT, gene delivery [227] MoS 2 Hydrothermal Gen 5 polyamidoamine (PAMAM) 420 nm (hd) -PTT, gene delivery [230] MoS 2 Exfoliation LA-PEG 100 nm (hd) 28.4 L g −1 cm −1 at 800 nm PTT, PDT, and PA imaging [231] MoS 2 Hydrothermal PEI Fe 3 O 4 ICG Pt(IV) 80 nm (hd) -PTT, PDT, PA, MRI imaging [234] WS 2 Exfoliation LA-PEG 3 ± 0.18 nm (l) -PTT, RT, PA, and CT imaging [179c] WS 2 Exfoliation BSA 20-100 nm (l) 4-5 nm (t) 21.8 L g −1 cm −1 at 808 nm PTT, PDT, and CT Imaging [186] WS 2 Exfoliation LA-PEG 50-100 nm (l) 1.6 nm (t) 23.8 L g −1 cm −1 at 808 nm PTT, PA, and CT imaging [189] WS 2 High-temperature reaction Gd 3+ C 18 PMH-PEG 90-100 nm (hd) 22.6 L g −1 cm −1 at 808 nm PTT, ...…”
Section: Metal Oxidesmentioning
confidence: 99%
“…Copyright 2017, Wiley‐VCH. d) Schematic illustration for the synthesis of G5‐MoS 2 nanoflakes and TEM images of MoS 2 nanoflakes . Copyright 2017, American Chemical Society.…”
Section: Tmdcs Surface Functionalization With Polymersmentioning
confidence: 99%